Metode Pengajaran Baca Al-Qur'an Di Indonesia Dalam Perspektif Pembelajaran Permulaan Bahasa Arab - Maftah Rozani (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2021)
Arabic and the Qur'an are like two sides of a coin that cannot be separated from one another, learning Arabic is a mandatory requirement for mastering the contents of the Qur'an and learning the language of the Qur'an means learning Arabic. However, 80% of the recipients of the Qur'an today are not Arabic speakers, while those who do not speak Arabic must continue to accept the Qur'an in its pure language, namely Arabic. This study uses a library research approach, which is a study carried out to solve a problem by using library materials. This type of scientific work contains a topic that contains ideas, which are supported by data obtained from library sources. Collecting study data sourced from books, magazines, newspapers, articles and so on, then analyzed using data analysis techniques. In this study, the conclusions: 1) In Indonesia, generally Hijaiyah letters are taught using the sound method, meaning that students are taught the sound of the letters instead of the alphabet. This tends to be more of a method of learning to read and write the Qur'an. 2) Although the main goal of Muslims is not to learn Arabic, but the method of teaching reading the Qur'an can be used to teach reading the beginning of Arabic because the author sees that there are similarities in the material to be delivered.